Pyrolytic Characteristics and Kinetics of Phragmites australis. (4th October 2011) - Zhao, Hui; Yan, Huaxiao; Zhang, Congwang; Liu, Xiaodong; Xue, Yanhui; Qiao, Yingyun; Tian, Yuanyu; Qin, Song
Abstract : The pyrolytic kinetics of Phragmites australis was investigated using thermogravimetric analysis (TGA) method with linear temperature programming process under an inert atmosphere. Kinetic expressions for the degradation rate in devolatilization and combustion steps have been obtained for P. australis with Dollimore method. The values of apparent activation energy, the most probable mechanism functions, and the corresponding preexponential factor were determined. The results show that the model agrees well with the experimental data and provide useful information for the design of pyrolytic processing system using P. australis as feedstock to produce biofuel.